FENOMENA BUDAYA POLITIK UANG PADA PEMILIHAN KEPALA DESA PERIODE TAHUN 2022-2028 DI DESA PADANG MAHONDANG KECAMATAN PULAU RAKYAT KABUPATEN ASAHAN - Silalahi, Indah My See; Panjaitan, Maringan; Degodona, L. Primawati (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The formation of the Tapanuli Province is one way to improve the welfare of the community through the acceleration of public services considering that the North Sumatra region is quite large and wide, so that areas far from the provincial capital experience obstacles in terms of provincial government services to the community, as a result, community welfare is always focused on areas around the city of Medan. This study aims to examine and analyze public services in the Tapanuli area, then the researcher conducts an analysis if the Tapanuli Province is formed, services to the community dealing with the provincial government will be easier to reach because the government will be close to each region. This paper uses a descriptive qualitative method. data obtained through literature studies and documentation. The results of this study indicate that with the realization of the provincial government to the Tapanuli region, the government's responsiveness in handling all problems and issues between districts/cities will be faster